Computational Modelling of Tyres Considering Operating and Safety Requirements - Jan Krmela (Communications - Scientific letters of the University of Zilina, 2008)
This contribution deals with the structural concept of tyres considering operating and safety aspects. Results obtained from experimental modelling of tyres considering operating and functional aspects are an essential condition of generation of “correct” computational models of tyres. Achievement of harmony between all requirements on the tyre and resulting demands on safety which would lead, apart from other things, to an increase of the life of the tyre, is a topical issue of computing algorithms in tyre-manufacturing plants.